Equilibrium adsorption isotherms of anionic, nonionic surfactants and their mixtures to shale and sandstone - Ahmed Muherei, Mazen (Canadian Center of Science and Education, 2009)
In this paper, the adsorptive behaviour of two surfactants (Triton X100 and SDS) and their mixtures (1:2; 1:1; 2:1 SDS:TX100 by wt) with two local adsorbents, sandstone and shale was examined. Adsorption of surfactants was assessed using a surface tension technique for aqueous phase surfactant concentrations less than critical micelle concentration (CMC). SDS (anionic surfactant) adsorption was not detected to any of the adsorbent samples. In contrast Triton X100, an ethoxylated nonionic surfactant, adsorbed to both adsorbents. Surfactant adsorbed/Kg adsorbent was lower for TX100-SDS mixtures in comparison to TX100 alone particularly for shale. Adsorption data for sub-micelle concentrations were found to fit successfully both Freundlich and Langmuir isotherms. Freundlich models pretty much represent the data than the Langmuir model. Because of their ability to minimize their amounts adsorbed to different adsorbents, mixed anionic-nonionic surfactant particularly TX100-SDS may show potential advantages in surfactant enhanced aquifer remediation (SEAR) and surfactant enhanced oil recovery (EOR) applications.